Board Gender, Experience and Education on Financial Performance: Evidence From Manufacturing Firms In Indonesia - Ovie Syafna Putri; Fitri Yeni; Ramdani Bayu Putra; Yosi Yulia (UPI YPTK Journal of Business and Economics, 2020)
This study aims to determine the effect of board gender, board experience and board education on financial performance in manufacturing firms in Indonesia. This research is quantitative. The total population is 168 manufacturing companies. A sample of 38 manufacturing companies was determined by using purposive sampling techniques. Research data was obtained from the financial statements of companies for the period 2015-2019. Data analysis techniques using a descriptive statistic, classical assumption test, estimation test and panel data regression. Hypotheses testing by using F-test dan t-test. The results showed that board gender did not affect company performance. The board experience and board education had a positive and significant effect on firms performance.